1998
DOI: 10.1109/58.677603
|View full text |Cite
|
Sign up to set email alerts
|

Velocity dispersion of acoustic waves in cancellous bone

Abstract: Measurement of ultrasonic attenuation and velocity in cancellous bone are being applied to aid diagnosis of women with high fracture risk due to osteoporosis. However, velocity dispersion in cancellous bone has received little attention up to now. The overall goal of this research was to characterize the velocity dispersion of human cancellous bone based on a spectral analysis of ultrasound transmitted through the bone specimens. We have followed a systematic approach, beginning with the investigation of a tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
2
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(100 citation statements)
references
References 24 publications
8
85
2
5
Order By: Relevance
“…This apparent negative dispersion observed in the nickel foams is consistent with the behavior in human calcaneal trabecular bone in vitro and in vivo. [13][14][15][16][17] Similar negative dispersion was also observed in trabecular-bone-mimicking phantoms consisting of parallel nylon wires and randomly distributed nylon filaments. 4,7 In contrast, Zhang et al found that the seven aluminum foams exhibited the positive dispersion at frequencies from 0.7 to 1.3 MHz while the other two foams displayed the minor negative dispersion.…”
supporting
confidence: 52%
“…This apparent negative dispersion observed in the nickel foams is consistent with the behavior in human calcaneal trabecular bone in vitro and in vivo. [13][14][15][16][17] Similar negative dispersion was also observed in trabecular-bone-mimicking phantoms consisting of parallel nylon wires and randomly distributed nylon filaments. 4,7 In contrast, Zhang et al found that the seven aluminum foams exhibited the positive dispersion at frequencies from 0.7 to 1.3 MHz while the other two foams displayed the minor negative dispersion.…”
supporting
confidence: 52%
“…14,15,17 Previous work has demonstrated, however, that when decomposed, the fast wave and slow wave each exhibit positive dispersion. 19,27 Negative dispersion has been measured not only in trabecular bone [29][30][31][32][33] and cortical bone 34 in vitro but also in trabecular bone-mimicking phantoms. 35,36 Several models have been proposed that predict negative dispersion including multilayer models, 31,37 multiple scattering models, 38 and independent scattering models.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the ultrasonic characteristics of bone to assess the risk of fracture due to osteoporosis are often based on the frequency dependence of attenuation ͑Droin et al, 1998;Langton et al, 1984;Wear and Armstrong, 2001͒. Bone attenuates ultrasound in a manner that is approximately linear with frequency ͑Droin et al., 1998;Wear, 2000a͒ so that the attenuation characteristics can be reported as a rate of change with frequency of the attenuation coefficient times the distance traveled, known as broadband ultrasound attenuation ͑BUA͒, or, if normalized with bone thickness, the normalized broadband ultrasound attenuation ͑nBUA͒.…”
Section: Introductionmentioning
confidence: 99%